Proteomics as an approach to the understanding of the molecular physiology of fruit development and ripening - Palma, José M.; Corpas, Francisco J.; del Río, Luís A. (Journal of proteomics, 2011)
Fruit ripening is a developmental complex process which occurs in higher plants and involves a number of stages displayed from immature to mature fruits that depend on the plant species and the environmental conditions. Nowadays, the importance of fruit ripening comes mainly from the link between this physiological process in plants and the economic repercussions as a result of one of the human activities, the agricultural industry. In most cases, fruit ripening is accompanied by colour changes due to different pigment content and increases in sugar levels, among others. Major physiological modifications that affect colour, texture, flavour, and aroma are under the control of both external (light and temperature) and internal (developmental gene regulation and hormonal control) factors. Due to the huge amount of metabolic changes that take place during ripening in fruits from higher plants, the accomplishment of new throughput methods which can provide a global evaluation of this process would be desirable. Differential proteomics of immature and mature fruits would be a useful tool to gain information on the molecular changes which occur during ripening, but also the investigation of fruits at different ripening stages will provide a dynamic picture of the whole transformation of fruits. This subject is furthermore of great interest as many fruits are essential for human nutrition. Thus far different maturation profiles have been reported specific for each crop species. In this work, a thorough review of the proteomic database from fruit development and maturation of important crop species will be updated to understand the molecular physiology of fruits at ripening stages. This article reviews from the academic and crop production points of view the contribution and future applicability of proteomics to the field of fruit ripening and development in agronomic species. [Display omitted]